Analysis of approval and disapproval of Aslah personal financing-i base on objective and subjective scoring methods / Bakhtiar Zainal - Zainal, Bakhtiar (Faculty of Business and Management, 2010)
The purpose of this study is to develop an understanding of how Bank Kerjasama Rakyat Berhad lend their credit to their customer. They are two approach that been used to make analyze and to find out about the credit information and history of their customer. The approach that being used is Credit Scoring and 5C’s credit evaluation (subjective score). According to Fisher (1936), credit scoring essentially a way of recognising the different groups in a population when one cannot see the characteristic that separates the groups but only related ones.